STRA6 regulates tumor immune microenvironment and is a prognostic marker in BRAF-mutant papillary thyroid carcinoma - He, Weiman; Sun, Yijia; Ge, Jiawei; Wang, Xuejie; Lin, Bo; Yu, Shuang; Li, Yanbing; Hong, Shubin; Xiao, Haipeng (Frontiers in Endocrinology, 2023)
Background: BRAF mutation is one of the most common genetic alterations contributing to the initiation and progression of papillary thyroid carcinoma (PTC). However, the prognostic value of BRAF mutation for PTC is limited. Novel markers are needed to identify BRAF-mutant patients with poor prognosis. Methods: Transcriptional expression data were downloaded from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets. Pathway enrichment was performed by Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis and gene set enrichment analysis (GSEA). Protein-protein interaction networks were predicted by the GeneMANIA. The correlation between STRA6 expression and immune infiltration was analyzed by tumor immune estimation resource (TIMER) and tumor-immune system interaction database (TISIDB). Immunohistochemistry was used to detect the STRA6 protein expression level of PTC. Infiltration of regulatory T cells (Tregs) and CD8+ T cells in tumor samples were analyzed by fluorescent multiplex immunohistochemistry. Results: In BRAF-mutant PTC, STRA6 was extremely upregulated and predicted unfavorable survival, which was an independent risk factor for increased mortality risk. Bioinformatic analyses indicated that STRA6 might activate the MAPK pathway synergistically with BRAFV600E. The expression of STRA6 was associated with immune infiltrates and T cell exhaustion. Fluorescent multiplex immunohistochemistry showed that STRA6 increased Tregs abundance and decreased CD8+ T cells infiltration in PTC. Moreover, STRA6 promoted epithelial-mesenchymal transition via increased cancer-associated fibroblasts infiltration. Conclusions: Our study demonstrates STRA6 may serve as a prognostic marker for BRAF-mutated PTC, which may drive thyroid carcinogenesis via activation of oncogenic pathway and regulation of tumor immunosuppressive microenvironment.